Preparation of Chitin Nanofibers and Natural Rubber Composites and Their Triboelectric Nanogenerator Applications - Kattaliya Petchnui; Teerayut Uwanno; Mayuree Phonyiem Reilly; Chinathun Pinming; Alongkot Treetong; Visittapong Yordsri; Nutthanun Moolsradoo; Annop Klamcheun; Winadda Wongwiriyapan (Materials, 2024)
Triboelectric nanogenerators (TENGs) have gained significant attention as promising energy-harvesting devices that convert mechanical energy into electrical energy through charge separation induced by friction and electrostatic induction. In this study, we explore the utilization of biowaste shrimp shell-extracted chitin nanofiber (ChNF) as a viable eco-friendly material for TENG applications. Composite materials were prepared by incorporating ChNF into natural rubber (NRL) at loading levels of 0.1 and 0.2 wt% (NRL/ChNF) to form the TENG triboelectric layer. ChNFs with a uniform width of approximately 10-20 nm were successfully extracted from the shrimp shells through a simple mechanical procedure. The NRL/ChNF composites exhibited enhanced mechanical properties, as evidenced by a higher Young's modulus (3.4 GPa) compared to pure NRL. Additionally, the NRL/ChNF composites demonstrated an increased dielectric constant of 3.3 at 0.1 MHz. Moreover, the surface potential difference of NRL increased from 0.182 V to 1.987 V in the NRL/ChNF composite. When employed as the triboelectric layer in TENG, the NRL/ChNF composites exhibited significant improvement in their output voltage, with it reaching 106.04 ± 2.3 V. This enhancement can be attributed to the increased dielectric constant of NRL/ChNF, leading to enhanced charge exchange and charge density. This study presents a straightforward and environmentally friendly technique for preparing sustainable natural materials suitable for energy-harvesting devices.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Supercapacitor Materials and Fabrication